Linking ocean and climate change governance. (13th April 2021) - Chan, Nicholas
Abstract: Increasing links are being made between ocean sustainability and climate change, as illustrated by the Intergovernmental Panel on Climate Change special report on the ocean and cryosphere, and the billing of the 2019 UN climate change conference as the "Blue COP." This review of these linkages is framed by the "bandwagoning" literature in global environmental politics to examine how ocean action has been constructed as being relevant for both climate mitigation and adaptation. This includes growing interest in "blue carbon" and the emerging narrative of the ocean as a "solution" to climate change, and drawing attention to climate impacts on ocean ecosystems and marine biodiversity. It highlights the roles played in constructing this link by entrepreneurial states and the NGO community in building an ocean‐climate bandwagon with the existing processes of the UN Framework Convention on Climate Change. As broader political attention is paid to ocean health, this review also highlights how these climate bandwagoning efforts overlap or clash with other ocean‐related international environmental processes. This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Abstract : The ocean and coastal ecosystems have been increasingly linked to the UN climate change negotiations. Source: https://pixabay.com/photos/sunset-beach-tropical-mangrove-tree-2947819/